Challenges and opportunities for next-generation sequencing in companion diagnostics. (February 2014) - Lin, Erick; Chien, Jeremy; Ong, Frank S; Fan, Jian-Bing
<x xml:space="preserve">Abstract</x> The rapid decline in sequencing costs has allowed next-generation sequencing (NGS) assays, previously ubiquitous only in research laboratories, to begin making inroads into molecular diagnostics. Genotypic assays – DNA sequencing – include whole genome sequencing, whole exome sequencing, focused assays that target only a handful of genes. Phenotypic assays comprise a broader spectrum of options and can query a variety of epigenetic modifications of DNA (such as ChIP-seq, bisulfite sequencing, DNase-I hypersensitivity site-sequencing, Formaldehyde-Assisted Isolation of Regulatory Elements-sequencing, etc.) that regulate gene expression-related processes or gene expression (RNA-sequencing) itself. To date, the US FDA has only cleared 12 DNA-based companion diagnostic tests, all in cancer. Although challenges exist for NGS in companion diagnostics, the wide-ranging capabilities of NGS offer extraordinary opportunities for the development and implementation of NGS-based companion diagnostics to probe oncogenes, tumor suppressor genes and cancer-enabling genes.